ANALISIS KETERJANGKAUAN DAN POLA SEBARAN SMA/SMK/MA NEGERI DI KABUPATEN TANGERANG MENGUNAKAN NEAREST NEIGHBOR ANALYSIS - Muhamad Kurniawan; Ira Megawati Gunawan Putri (Balai Diklat Keagamaan Medan, 2023)
The development of educational facilities in an area must be considered optimally in accordance with national regulatory standards so that it makes it easier for the community to access these facilities. This study aims to understand and describe affordability, the distribution pattern of location points for SMA/SMK/MA Negeri in Tangerang Regency and to find out the relationship between the population aged 15-19 years for each sub-district in Tangerang Regency using a quantitative descriptive research method with a spatial approach. The affordability analysis resulted in 76.05% of residential areas not being reached, with a random pattern of location points and no correlation between the location points of State SMA/SMK/MA and the population aged 15-19 years with a correlation index value of 0.106.